Pola Jaringan Komunikasi Organisasi dalam Meningkatkan Kualitas Pelayanan Kesehatan: Studi di RSIA Murni Teguh Rosiva, Medan - Yudiyanto, Ade Rachmat; Kholil, Syukur (Jurnal Studi Ilmu Sosial dan Politik, 2024)
Purpose: This study aims to examine communication patterns at Murni Teguh Rosiva Mother and Child Hospital (RSIA) in Medan, focusing on the effectiveness of organizational communication models as outlined by Fred C. Lunenburg, including chain, wheel, circle, Y, and all-channel communication structures, in supporting coordination, responsiveness, and healthcare service quality. Methodology/approach: A qualitative approach was employed, involving in-depth interviews and participatory observation with both medical and non-medical staff. Data collection focused on analyzing communication patterns within the hospital setting. Results/findings: The study revealed that each communication model presents unique strengths and limitations in facilitating information flow and decision-making processes. The chain and wheel models support structured information distribution but often result in delays during critical situations. The circle and Y patterns enable faster inter-unit collaboration but are susceptible to miscommunication due to varying professional backgrounds. The all-channel pattern in informal communication fosters staff solidarity but risks the spread of inaccurate information. Limitations: This study is limited to observational and interview-based data from a single healthcare institution, potentially restricting generalizability across different healthcare settings. Contribution: This research contributes to the development of a more responsive and collaborative communication system in healthcare institutions, particularly in enhancing operational support through adaptive communication frameworks.